Penerapan Think Pair Square Berbantuan Infografis untuk Meningkatkan Hasil Belajar Siswa XI 8 SMAN 6 Mataram - I Ketut Arimbawa; Ni Made Novi Suryanti; Jepri Utomo; Husnayain Husnayain (Lembaga Sosial Rumah Indonesia, 2026)
Purpose – This research addresses the low Sociology learning outcomes of class XI 8 students at SMAN 6 Mataram, where initially only 63% (21 out of 33) achieved the Learning Objectives Achievement Criteria (KKTP) score of 78 due to learning process dominated by the lecture method causing students to be passive and struggle with applying theoretical concepts. This study aimed to improve student outcomes by implementing the infographic-assisted Think Pair Square (TPS) cooperative learning model.Methods – This Classroom Action Research (CAR) involved 33 students across two cycles, each consisting of planning, acting, observing, and reflecting stages. Data was collected through model implementation observation sheets and essay tests. Success indicators were set at 100% for model implementation and 75% for classical learning completeness.Findings – The findings reveal a critical link between syntax fidelity and results. Cycle I failed with only 43% model implementation and 66% learning completeness because the 'Pair' stage was omitted. Following corrective actions, Cycle II achieved 100% implementation, propelling classical completeness to 96% (26 out of 27 students). This confirms that infographic-assisted TPS significantly enhances learning outcomes when implemented correctly. Research Implications – This research emphasizes the importance of teachers adhering closely to the Think Pair Square syntax, especially the 'Pair' stage, which provides pupils with a crucial cognitive bridge. To enhance student engagement and learning performance, teachers must become active facilitators rather than passive spectators.